PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI PADA SISWA - Rhamadani, Qhulbi; Syam, Faradillah; Nurindah; Syamsiah (Almeera Education, 2023)
This study aims to improve student biology learning outcomes by using the Discovery Learning learning model on Virus material in class X.4 of SMA Negeri 10 Maros. This research is a class action research that has been carried out in as many as 2 cycles. The subjects taken are all students of grade X.4 of SMA Negeri 10 Maros for the 2023/2024 school year. Data collection techniques in this study are (a). observation, (b). interview, (c). documentation, and (d). test. Based on the results of the study, it can be concluded that the percentage of student learning completeness is in the very good category, so it can be said that Discovery Learning is effectively used on Virus material, this is shown in cycle 1 the percentage of learning completeness is 00.0%, and in cycle 2 it increases to 100%. In the activities of students and teachers based on the results of observations and also on the model used by researchers, Discovery Learning is at an effective level.